Processing of Corn Tortilla Chips with Appropriate Technology as Diversification of Crop Yields to Increase Farmers' Income in Pematang Simalungun - Dalimunthe, Amirhud; Situmorang, Benyamin; Fridiarty, Lelly; Purba, Rasita (Universitas Negeri Medan, 2023)
Processing of agricultural products is important to increase added value, especially when production is abundant and prices are low. The increase in added value in the form of various corn products can stimulate the development of micro, small and medium enterprises. Community empowerment through increasing post-harvest knowledge and capabilities in processing various corn products in particular can be the basis for community economic development. One of the processed corn products that consumers like is Corn Tortilla. The product processing process with appropriate technology is quite simple so that it has the opportunity to be adopted by rural communities, especially corn farmers as a home industry. The purpose of this PKM activity is to develop the business of corn farmers in Pematang Simalungun Village into an economically independent business through corn tortilla processing activities, design of boiled corn milling machine, design of ampia machine, spinner machine, and production training. The approach method used is the method of education, design, production training, business management training, and mentoring. The specific target achieved was to produce a boiled corn milling machine to increase the effectiveness of abundant corn production into corn tortilla products and business management capabilities. As a result, corn farmers can process abundant agricultural products into Corn Tortilla products